2017
DOI: 10.1111/nph.14505
|View full text |Cite
|
Sign up to set email alerts
|

Covariation and phenotypic integration in chemical communication displays: biosynthetic constraints and eco‐evolutionary implications

Abstract: Chemical communication is ubiquitous. The identification of conserved structural elements in visual and acoustic communication is well established, but comparable information on chemical communication displays (CCDs) is lacking. We assessed the phenotypic integration of CCDs in a meta-analysis to characterize patterns of covariation in CCDs and identified functional or biosynthetically constrained modules. Poorly integrated plant CCDs (i.e. low covariation between scent compounds) support the notion that plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
98
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 75 publications
3
98
0
Order By: Relevance
“…). A recent meta‐analysis indicated that floral volatile profiles are, on average, the most variable of all plant or animal volatile blends examined (Junker et al ., ). Our data suggest that nectar microbes can contribute to this variability.…”
Section: Discussionmentioning
confidence: 99%
“…). A recent meta‐analysis indicated that floral volatile profiles are, on average, the most variable of all plant or animal volatile blends examined (Junker et al ., ). Our data suggest that nectar microbes can contribute to this variability.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, qualitative intraspecific variation is much lower than interspecific variation (Junker et al. ; Kuppler et al., ) because each plant species adds new compounds to communities (Junker, ). Accordingly, in our samples most substances were emitted by only one or a few plant species, resulting in a zero‐inflated matrix and thus preventing a meaningful analysis; therefore, we grouped the compounds according to their biosynthetic origin and their functional groups: aliphatics (A), aromatics (AR), C5‐branched pathway (C5), irregular terpenes (IT), monoterpenes (MT), sesquiterpenes (ST) (Table S4, S5).…”
Section: Methodsmentioning
confidence: 99%
“…In a compilation of a large number of studies Junker et al . (in this issue, pp. 739–749) took a pioneering step to approach the diversity of VOCs as a trait that can be used for comparative studies in ecology and evolution.…”
mentioning
confidence: 99%
“…One of the major conclusions of this study by Junker et al , was that we are, at best, at the beginning of understanding how chemical information is encoded, although we have a large number of studies that seem to be able to assign a particular function to a particular VOC or group of VOCs. The multifunctionality that seems characteristic to most secondary metabolites, and the likely context dependency of each compound in a particular chemical and ecological environment, makes the identification of common principles of chemical information difficult.…”
mentioning
confidence: 99%
See 1 more Smart Citation